Symposium 8: Meeting over Cultural Boundaries: Networked Learning for Sustainable Development - Nordén, Birgitta; Hansson, Birgit (Proceedings of the International Conference on Networked Learning, 2006)
The purpose of our research is to analyze and describe the ways in which the students experienced their learning process in the field of sustainable development in the Young Masters Program, using a phenomenographic approach to the research. We are focusing in particular on the ways in which the meeting between the course materials, the intercultural discussions and the students’ own life-experiences constitute a context for learning, with emphasis on the diversity that is supported by the course. Data are collected from the students’ assignments and follow-up discussions where they reflect on the assignments in the course’s online meeting place. A learning perspective on the communication is in focus.